Dental students ‘experiences of remote emergency online learning at the University of the Witwatersrand during the covid-19 pandemic - Tshite, Koketso (My University, 2024)
Background-The Covid-19 pandemic presented unprecedented challenges that could provide opportunities to improve dental education. Most papers reporting these challenges and opportunities came from high-income countries, so exploring students’ experiences during emergency remote learning (ERL) in low-resource settings is imperative. Methods- A descriptive, cross-sectional, online survey was sent to 154 Bachelor of Dentistry students at the University of the Witwatersrand in October 2020. The questionnaire included open- and closed-ended questions. Quantitative data were analysed using descriptive and inferential tests. The open-ended responses were analysed using content analysis. Summary of results The response rate for the survey was 67.5% (99/154). There was a significant difference across the five years of study between urban and rural locations during ERL and the type of internet connection the respondents used. Respondents’ preferred teaching modalities changed from before to after ERL, with more preferring blended learning over contact or fully online learning. Conclusions- The tumult created by the sudden shift to ERL should be viewed as a learning curve to broaden our knowledge of how best to harness the affordances of online learning. The exposure to online learning appears to have shifted dental students’ preferences towards combined online and contact learning. More blended learning has implications for integrating online learning into the dental curriculum in ways that enhance learning and requires broader institutional support. Recommendations are made for ways that such support could be provided.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Health Sciences Education to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Emergency remote learning (ERL); COVID-19; Dental students; SDG-3: Good health and well-being